Style of education and communication In the perception of young people by single mothers - Napora, Elżbieta; Kozerska, Agnieszka (Studia Psychologica: Theoria et praxis, 2010)
Puropse of researches was to single out a group of lonely mothers and explain which educational style and way of communication with adole scents they prefer. 99 opinions were collected, which described in analise. Results show, that single mothers prefer liberał educational style which is connected with problems in communication, and autocratic style is connected with opened communication and is very often preferred by mothers. Democratic style is chosen seldom. Fixture of mothers to 3 concen trations is connected with education, place of living and time of father’s absence.